Correction of humoral immunity dysfunctions in patients with chronic tonsillitis and diabetes mellitus - Vdovichenko, N; Tupotilov, O; Boyko, A; Kolyada, O (Annals of Mechnikov’s Institute, 2020)
In the therapy of various forms of chronictonsillitis (CT) were used asimmunomodulatory agentsRespibron and Licopid. Diabetes mellitus type 1 (also known as type 1 diabetes, or T1DM) is one of the important factors that couldsignificantly complicate the therapy of chronic tonsillitis.T1DM is a form of diabetes mellitus that results from the autoimmune destruction of the insulin-producing beta cells in the pancreas. The aim of our study was to explore thedynamics of immunologic indicators during the activedisease and treatments in patients with various forms of chronic tonsillitis, including tonsillitiscomplicated with T1DM. Materials and methods. 64 patients with various forms of chronic tonsillitisin active period of disease observed during the study.Patients were divided into the following groups: 21persons with the compensate form of CT (CTC), 24 persons with the decompensate form of CT (CTD) and 9 persons with thedecompensate form of CT complicated with T1DM (CTD+ T1DM). The control group consisted of 15apparently healthy persons. Concentrations of sIgA and IgA in the oropharyngeal secret were determined by the method of radialimmune diffusion by Manchini. Lysozyme content was determined using the test system "Lysozyme" ("Reakompleks", Russia). Levels of lactoferrin and SLPI in the oropharyngeal secret of patients wereevaluated using ELISA test systems of "BioChemMack", Russia. Patients of group CTC were divided into subgroups CTC1 andCTC2, depending on the applied treatment. Bothsubgroups treated with standard therapy for two weeks, on the fifteenth day of therapy patients of subgroupCTC2received Respibronduring 10 days by 1 tablet once a day and Licopidduring 10 days by 1 mg once a day. Similarly patients of group CTD were divided into subgroups CTD1 andCTD2. Patients of subgroupCTD2received therapy according to the scheme of CTC2. Patients of group CTD+ T1DM divided into subgroups CTD1+ T1DM and CTD2+ T1DM. Patients of subgroup CTD2+ T1DMreceived therapy according to the scheme of CTC2. The effectiveness of the treatment wasassessed by the general state of the patients according tooropharyngoscopy and humoral immunity after 45 days of observation. Statistical analysis ofthe results was performed using the Mann-Whitney Utest. According to the accepted level of reliability indexvalue between the groups (p), which constituted or wereless than 0.05. Results and discussion. As a result of immunological studies, it was determined that the exacerbation of chronic process in oropharyngeal mucosa is characterized by immunological failure, such as reduced levels of sIgA, IgA and IgG in the oropharyngeal secret.Content of SLPI in patients with CT before treatment was significantly below control values. Lysozyme level before treatment was significantly reduced in groups CTD and CTD+T1DM. Lactoferrin level was increased in groups CTC and CTD, but in group CTD+ T1DM it was reduced. According to our study, patients with CT combined with diabetes had reduced levels of sIgA, IgA, lysozyme, lactoferrin and SLPI, but elevated levels of IgG. After standard therapy content of almost all measured parameters in experimental groups differed from controls. The level of sIgA was reduced relative to control group and before treatment. IgA level was reduced in the group CTD1 + T1DM relative control, but significantly higher relative indicators before treatment in groups CTD1and CTD1 + T1DM. The level of IgG in groups CTC1and CTD1 was increased relative to control group and in groups before treatment. In the group CTD1 + T1DM levels of IgG were decreased relative before treatment, but were higher than the control. The level of lysozyme after standard therapy did not differ from the control except group CTD1 + T1DM and was significantly higher than the corresponding values before treatment in all groups. The level of lactoferrin in groups CTC1 and CTD1 did not differ from control, but significantly different from the values before treatment. In the group CTD1 + T1DM lactoferrin level was reduced relative to control, but had dynamics other than groups without diabetes. In CTC1 and CTD1 groups its level before treatment was increased and after the therapy was decreased, in group CTD1 + T1DM we observed the opposite trend. The level of SLPI in all groups was reduced relative to control, but significantly higher than before treatment. Patients of groups CTC2, CTD2 and CTD2 + T1DM in addition to standard therapy on the fifteenth day of therapy received "Respibron" and "Licopid." The level of sIgA in groups without diabetes did not differ from the control group and in group CTD2 + T1DM was reduced relative to control, but significantly higher than before treatment and in group CTD1 + T1DM that shows the influence of immunomodulatory agents. IgA levels did not differ from the control in all groups. The level of IgG in groups CTC2 and CTD2 was increased relative to control and indicators before treatment, in group CTD2 + T1DM IgG levels decreased relative before treatment. Lysozyme and lactoferrin level after treatment with immunomodulators did not differ from controls in all groups. The level of SLPI in groups CTD2and CTD2 + T1DM was reduced relative to control but significantly higher than before treatment. Clinical and immunological evaluation of complex treatment of patients with CT in acute stage by proposed scheme including preparations "Respibron" and "Licopid" and also with T1DM in the anamnesis showed the effectiveness of its use.